Trauma and conflict as prerequisites for identity transformation - lessons from the South African Partnership for Missional Churches - Hendriks, HJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
This paper researches the process of identity transformation that is taking place in mainline congregations in post-apartheid South Africa. I is a descriptive study of the growth in the South African Partnership for Missional Churches and describes the transformation by making use of the pattern found in the Psalms: orientation-disorientation-reorientation transition, The research will test the following hypotheses that are viewed as prerequisites for identity transformation: -Trauma and conflict caused by new power structures in society were the necessary disorientating forces that led to a theologically-based reorientation in churches; -The change in theological epistemology led to a new culture of doing theology (including the way church meetings are held); -Other prerequisites for a change in identity within the Southern African scenario are: leadership, the crossing of boundaries, the art of listening to “the other” and the mystery and motivation of the movement of the Spirit of God.